Slavistična prepletanja 5 (University of Maribor Press, 2024)
Slavic Intertwining 5. The scientific monograph Slavic Intertwining 5 contains thirteen contributions divided into four thematic sections. The monograph begins with a series of contributions exploring the Slovene language in a diachronic, synchronic and digital context, while comparative phraseological research is the focus of the second section. The third section contains contributions on the teaching and learning Slovene as a non-first language, especially in the South Slavic language area. The monograph is rounded off by a section that touches on poststructuralist approaches to the study of language, gender and sexuality and discusses the lexicographical representation of words in relation to LGBTIQ+ persons.